MARKETING PUBLIC RELATIONS STRATEGY OF PT. JANIK LAMPUNG IN BUILDING BRAND IMAGE - Nabila Shofi Aini; Iva Fikrani Deslia (Universitas Muhammadiyah Jakarta, 2025)
Marketing Public Relations (MPR) is a strategic approach that integrates marketing activities with public relations to build a strong and positive brand image. This strategy has significant potential to enhance the company's brand image, which in turn contributes to increased profitability. PT. Janik Lampung is a company operating in the fashion industry, focusing on the preservation and innovation of Tapis Lampung, a cultural product that not only reflects the beauty of traditional art but also conveys the philosophical values and identity of the Lampung community. This study aims to analyze the Marketing Public Relations strategy implemented by PT. Janik Lampung in its effort to build a strong brand image. The research employs Whalen’s 7 Steps of Strategic Planning as the theoretical framework and utilizes a qualitative method, collecting data through interviews, data categorization, and social media content analysis. The findings reveal that PT. Janik Lampung applies a systematic combination of Pull, Push, and Pass strategies in each planning stage. These steps include situational analysis using SWOT, goal setting based on SMART principles, strategy formulation, audience targeting, communication message planning, selection of social media tactics, and the evaluation of communication effectiveness. The key messages and hashtags #BanggaBerbudaya (Proud of Culture) and #SobatLestariBudaya (Culture Sustainability Companions) have been effectively embedded in the minds of consumers, fostering increased awareness, engagement, and loyalty toward Tapis Lampung products. This strategy has succeeded in strengthening the brand image of Janik Lampung as an authentic local brand that aligns with modern market preferences, particularly among Generation Z. Consequently, Janik Lampung has demonstrated its competitiveness in both local and national markets as a cultural based creative industry player. Keywords: Brand Image, Marketing Public Relations, Social Media, Tapis Lampung, Whalen’s 7 Steps of Strategic Planning